“You Don’t Have to Be Filmish”: The Toronto Jewish Film Festival - Koven, Mikel (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1999)
The Toronto Jewish Film Festival is a one-week celebration of Judaism and Cinema that occurs in downtown Toronto, at the Bloor Cinema, early every May. The folkloristic literature on festival notes that these kinds of events are ways that communities and groups celebrate themselves, and although film festivals are frequently excluded from consideration of traditional festivity, I shall demonstrate that such an omission is unfortunate, since like traditional festivity, film festivals, in particular ethnic film festivals, explore the same issues of liminality for the celebrating culture.